Kajian Yuridis Terhadap Anak Yang Karena Kelalainnya Mengakibatkan Matinya Orang - Briant Marino Paliama; Margie Gladies Sopacua; Elias Zadrach Leasa (Faculty of Law Universitas Pattimura, 2023)
Children are the hope for the nation, which means that children are the next generation of the nation. Children who are also citizens have rights and obligations. As the nation's successor, children have the right to protection, both from the state and from the family. Nowadays, there are many children who become perpetrators of traffic violations, causing traffic accidents. Child cases in context with the law are suspected of being criminal offenses. Children who become perpetrators of traffic accidents are entitled to protection, including legal protection. The research method used in this writing is normative juridical, the problem approach used is a statutory approach, case approach, conceptual approach, comparative approach and historical approach, the legal materials used are primary legal materials, secondary legal materials and tertiary legal materials, the procedure for collecting legal materials in this research is carried out by conducting literature studies, managing and analyzing legal materials using qualitative data analysis techniques. The results of the discussion of this writing, that the child can be criminally responsible in the presence of a separate process that is not the same as processing adults, by means of the implementation of the juvenile criminal justice system (SPPA) carried out based on the principles of protection of justice, non-discrimination and the best interests of the child, the development of children's motor skills is a facult.